2004
DOI: 10.1182/blood-2003-10-3560
|View full text |Cite
|
Sign up to set email alerts
|

Better outcome of adult acute lymphoblastic leukemia after early genoidentical allogeneic bone marrow transplantation (BMT) than after late high-dose therapy and autologous BMT: a GOELAMS trial

Abstract: , for the GOELAMS (Groupe Ouest-Est des Leucé mies Aiguë s et Maladies du Sang) GroupVarious transplantation strategies have been designed to improve the poor prognosis of adult (ages 15 to 60 years) acute lymphoblastic leukemia (ALL). The GOELAL02 trial evaluated the impact of early allogeneic bone marrow transplantation (alloBMT) or delayed unpurged autologous stem cell transplantation (ASCT) for patients who had no human leukocyte antigen (HLA)-matched sibling donor or who were older than 50 years. Inclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
150
2
9

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(168 citation statements)
references
References 47 publications
7
150
2
9
Order By: Relevance
“…Advances in the chemotherapeutic treatment of adult acute lymphoblastic leukemia (ALL) have resulted in complete remission (CR) rates in the range of 74-93%; however, only 35% of these patients achieve long-term disease-free survival (DFS) [1][2][3][4][5][6][7]. Because a high incidence of relapse is the main cause of treatment failure in adults with ALL, the use of allogeneic stem cell transplantation (SCT) as post-remission therapy has become a widely-accepted strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Advances in the chemotherapeutic treatment of adult acute lymphoblastic leukemia (ALL) have resulted in complete remission (CR) rates in the range of 74-93%; however, only 35% of these patients achieve long-term disease-free survival (DFS) [1][2][3][4][5][6][7]. Because a high incidence of relapse is the main cause of treatment failure in adults with ALL, the use of allogeneic stem cell transplantation (SCT) as post-remission therapy has become a widely-accepted strategy.…”
Section: Introductionmentioning
confidence: 99%
“…The study results certainly depend on the compared "conventional" treatment approach. Some groups scheduled autologous (auto) SCT only 25 and others a randomized comparison of auto SCT and chemotherapy. 4,6,14,26 The preferable approach for this trial design is "intentto-treat" analysis that compares patients with donors to those without donors.…”
Section: Stem Cell Transplantationmentioning
confidence: 99%
“…OS of studies with "genetic randomization" is not superior to chemotherapy studies (see above), which is partly due to the fact that allo sib SCT could be realized in only 11-38% of the patients. [4][5][6]14,25,26 Even if allo sib SCT yielded favorable results, due to infrequent realization the impact on overall outcome is too small.…”
Section: Stem Cell Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown 1,2 that results of autologous hematopoietic stem cell transplantation (HSCT) in adult ALL [3][4][5][6][7][8][9][10][11][12][13][14] can be improved by administering post transplant maintenance chemotherapy with 6-mercaptopurine (6-MP), methotrexate and vincristine-prednisone. A recent review of autologous HSCT in ALL 15 suggested that the value of autotransplantation is likely to be underestimated in ALL.…”
Section: Introductionmentioning
confidence: 99%